Mechanical and microstructural behavior of brazed aluminum / stainless steel mixed joints. Issue 1 (March 2016) - Fedorov, V; Weis, S; Wagner, G
Abstract: There is a requirement to combine different materials such as aluminum and stainless steel in industrial applications like automotive heat exchangers. Brazing offers the possibility to reduce the joining temperature in comparison to welding due to the lower liquidus temperature of the fillers. In the present work, the mechanical and microstructural behavior of aluminum / stainless steel mixed joints is investigated. The specimens are produced by induction brazing using an AlSi10filler and a non-corrosive flux. To evaluate the mechanical properties of the joints, tensile tests at elevated temperatures are carried out. Additionally, long-term thermal exposure experiments are done in order to investigate the changes in the microstructure.